Breeding dispersal in a resident boreal passerine can lead to short‐ and long‐term fitness benefits. Issue 9 (21st September 2021) - Fuirst, Matthew; Strickland, Dan; Norris, D. Ryan
Abstract: Whether an individual disperses or remains site‐faithful between breeding seasons can have important impacts on individual fitness and population dynamics. While several studies have identified factors influencing the probability of breeding dispersal, the consequences of dispersal are much less certain, particularly over an individual's lifetime. Here, we use 81 cases (13 paired and 55 single dispersals) of breeding dispersal across 55 yr of breeding and re‐sighting data from an individually marked population of Canada jays ( Perisoreus canadensis ) at the southern edge of their range in Algonquin Provincial Park, Ontario to determine both the short‐ (year after dispersal) and long‐term (lifetime) consequences of breeding dispersal. In the year following dispersal, adults had larger brood sizes and higher nest success compared to the year prior to dispersal. However, when adults dispersed during the fall/winter, they had significantly later lay dates and lower rates of nest success than adults that dispersed during the summer. Additionally, most breeders dispersed to territories of higher quality and individuals that dispersed to a territory of lesser quality experienced lower rates of nest success. Importantly, individuals that dispersed at least once in their lifetime produced an average of 2.7 more young and recruited an average of 0.9 more juveniles into the population compared to individuals that remained site‐faithful. Our study provides rare evidence of both the short‐ and long‐term benefits of breeding dispersal in Canada jays and demonstrates how the timing of dispersal can also have consequences for individual reproductive performance.